Software in distance education course ``Probability theory and statistics’’ - Dabulytė-Bagdonavičienė, Jurgita; Bikulčienė, Liepa (Lietuvos matematikos rinkinys, 2004)
After evaluation of the results of students questioning the distance learning course ``Probability theory and Statistics’’ was renewed supplementing it with new elements. In the paper it is presented the most important of them: lab works using software Mathcad and video lessons using software ViPS. Good results of the students in 2002/2003 academic year have enabled to provide the distance education course ``Probability theory and Statistics’’ for the students of two faculties of Kaunas University of Technology. Lab works and video lessons are also widely used by regular students. The second year students took part in this analysis.